On the evaluation of stratification based entropy optimized hydromagnetic flow featuring dissipation aspect and Robin conditions. (July 2020) - Khan, W.A.; Waqas, M.; Kadry, S.; Asghar, Z.; Abbas, S.Z.; Irfan, M.
Highlights: Double stratification impact in nonlinear convective second grade nanoliquid is modeled. Viscous dissipation and Joule heating are considered to model energy expression. The idea of entropy generation along with binary chemical reaction is introduced. Results obtained are illustrated and interpreted. Abstract: Background and objective: The scrutiny of nonlinear convected flow aspect has continuously appealed researchers attention because of its ample demands in processes like heat exchangers, building insulation, crystal growth, insulation of nuclear reactor, food processing, solar energy and electronic element chilling etc. Taking into consideration the aforesaid utilizations, we modeled differential type (second-grade) nanoliquid considering non-linear mixed convection. The considered differential type nonlinear model elaborates viscoelasticity (elastic and viscous) characteristics. Furthermore the thermal systems emphases on transportation of heat and irreversibility reduction. Especially, evaluating the systems via thermodynamic second relation is essential with the purpose of finding a standard communication between power input prerequisite and heat transference augmentation. Method: Formulated non-dimensional problem is non-linear subject to the assumptions (i.e., Non-linear mixed convection, magnetic field, viscous dissipation, double stratification, Joule heating and convective conditions). Analytic simulations for modeled non-linear systems is not possible. Hence we considered bvp4c scheme for non-linear analysis. Conclusions: Velocity ( f ′ ( η ) ) of second grade (non-Newtonian) fluid intensifies for larger estimations of R * and λ * whereas it dwindles for M . Temperature of nanoliquid deteriorates with S 1 while ( θ ( η )) rises against Ec . Entropy generation (EG) and (BN) (Bejan number) significantly affected by physical parameters M, α 2 and Br .